2005
DOI: 10.1007/s00467-004-1807-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3A and 2B6 in the developing kidney: implications for ifosfamide nephrotoxicity

Abstract: Repeated administration of agents (e.g., cancer chemotherapy) that can cause drug-induced nephrotoxicity may lead to acute or chronic renal damage. This will adversely affect the health and well-being of children, especially when the developing kidney is exposed to toxic agents that may lead to acute glomerular, tubular or combined toxicity. We have previously shown that the cancer chemotherapeutic ifosfamide (IF) causes serious renal damage substantially more in younger children (less than 3 years of age) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 53 publications
0
57
0
1
Order By: Relevance
“…The Ciona genes also are expressed at different stages of development indicating a potential stage-specific functional role. Previous studies have demonstrated the developmental expression of multiple CYP3As (Stevens et al, 2003;Aleksa et al, 2005). Thus, CYP3A4 and CYP3A7 are expressed specifically in adult and fetal human livers, respectively (Komori et al, 1990), and distinct CYP3As are differentially expressed in embryonic and adult fish (Kullman and Hinton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The Ciona genes also are expressed at different stages of development indicating a potential stage-specific functional role. Previous studies have demonstrated the developmental expression of multiple CYP3As (Stevens et al, 2003;Aleksa et al, 2005). Thus, CYP3A4 and CYP3A7 are expressed specifically in adult and fetal human livers, respectively (Komori et al, 1990), and distinct CYP3As are differentially expressed in embryonic and adult fish (Kullman and Hinton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A5 and CYP2B6 activities are present in kidney and liver (12,13). The calculated [CAA] in rat renal cortex is f15 Amol/L following daily injection of 50 mg/kg IFO for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…IFO must be oxidized by cytochrome 3A5 (CYP3A5) and CYP2B6 oxidase to acquire an antineoplastic activity (11,12). The oxidation of IFO occurs via two major routes: (a) at the cyclic carbon-4, resulting in the formation of 4-OH-IFO, which is then decomposed to isophosphoramide mustard (IPM) and acrolein (1,2); and (b) via the side chain dechlorethylation, which leads to formation of chloroacetaldehyde (CAA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated tissue concentration of these toxins promotes injury through both direct toxicity and ischemic damage (reduced prostaglandins, increased thromboxane). Biotransformation of drugs, xenobiotics, and other substances by multiple renal enzyme systems, including CYP450 and flavin-containing monooxygenases, favors the formation of toxic metabolites and reactive oxygen species (33)(34)(35). The presence of these byproducts of metabolism tilts the balance in favor of oxidative stress, which outstrips natural antioxidants and increases renal injury via nucleic acid alkylation or oxidation, protein damage, lipid peroxidation, and DNA strand breaks (33)(34)(35).…”
Section: Kidney-specific Factorsmentioning
confidence: 99%